Attributes influencing parental decision-making to receive the Tdap vaccine to reduce the risk of pertussis transmission to their newborn - outcome of a cross-sectional conjoint experiment in Spain and Italy - Edouard Ledent; Giovanni Gabutti; Esther W. de Bekker-Grob; Juan Luis Alcázar Zambrano; Magda Campins Martí; María Teresa Del Hierro Gurruchaga; María José Fernández Cruz; Giuseppe Ferrera; Francesca Fortunato; Pierfederico Torchio; Giorgio Zoppi; Christian Agboton; et al. (Taylor & Francis Group, 2019)
Pertussis vaccination of parents and household contacts ('cocooning') to protect newborn infants is an established strategy in many countries, although uptake may be low. Many aspects may influence such decision-making. We conducted a cross-sectional survey (NCT01890447) of households and other close contacts of newborns aged ≤6 months (or of expectant mothers in their last trimester) in Spain and Italy, using an adaptive discrete-choice experiment questionnaire. Aims were to assess the relative importance of attributes influencing vaccine adoption, and to estimate variation in vaccine adoption rates and the impact of cost on vaccination rates. Six hundred and fifteen participants (Spain, n = 313; Italy, n = 302) completed the survey. Of 144 available questionnaire scenarios, the most frequently selected (14% of respondents in both countries) were infant protection by household vaccination at vaccination center, recommendation by family physician and health authorities, with information available on leaflets and websites. The attribute with highest median relative importance was 'reduction in source of infection' in Spain (23.1%) and 'vaccination location' in Italy (18.8%). Differences between other attributes were low in both countries, with media attributes showing low importance. Over 80% of respondents indicated a definite or probable response to vaccine adoption (at no-cost) with estimated probability of adoption of 89-98%; applying vaccine costs (25€ per person) would reduce the probability of uptake by 7-20% in definite/probable respondents. Awareness of these determinants is helpful in informing Health Authorities and healthcare practitioners implementing a cocooning strategy for those populations where maternal immunization is not a preferred option.